A wear-resistant and tear-resistant mountaineering garment fabric and a manufacturing method thereof
Patent Information
- Application Number
- CN202611404515.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-23
AI Technical Summary
为提升面料的抗撕裂性能及耐磨性能,一般选择通过织物结构优化、功能膜层压复合或表面涂层设置等方式,这些方式中,如织物结构优化会增加织物克重,不利于轻量化,而表面涂层设置会影响织物的透气透湿性,降低舒适度,而功能膜的层压复合会考验膜与面料件的结合牢度,从而影响面料的使用耐久性,基于上述技术问题的存在,本发明提出了一种耐磨、抗撕裂的登山服面料及其制作方法
本发明通过沿基底膜经向平行走线缝合多个复合金属丝线A,再对复合金属丝线A于基底膜上的缝合段中沿纬向布置至少一个复合金属丝线B,构建获得交织增强层,并于基底膜两侧交织增强层分别依次放置硅烷接枝α-聚烯烃热熔胶膜和涤棉面料,再通过热压复合工艺复合获得面料;通过交织增强层构建“增强网络”使面料抗撕裂性能的提升的同时,再通过硅烷接枝α-聚烯烃热熔胶膜的设置,加强交织增强层的结构强度以促进面料的抗撕裂性能及耐磨性能的整体提升,面料整体的使用耐久性好,可促进面料抗撕裂性能及耐磨性能的长久发挥。
Smart Images

Figure CN122956831A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fabric technology, specifically to a wear-resistant and tear-resistant mountaineering clothing fabric and its manufacturing method. Background Technology
[0002] Outdoor sports fabrics are an important branch of functional textiles, designed to provide protection, comfort, and durability for various outdoor activities. They can be further subdivided according to the sport, such as skiwear fabrics and mountaineering fabrics. Mountaineering fabrics, in particular, are high-performance materials designed specifically for extreme outdoor environments. Their fabric structure often employs a "sandwich" structure of microporous membranes to achieve a balance of waterproof, breathable, and windproof properties. Furthermore, for safety reasons, mountaineering fabrics generally also require tear resistance and abrasion resistance, which presents new challenges for their development. To improve the tear resistance and abrasion resistance of fabrics, methods such as fabric structure optimization, functional membrane lamination, or surface coating are generally chosen. Among these methods, fabric structure optimization increases the fabric weight, which is not conducive to lightweighting, while surface coating affects the breathability and moisture permeability of the fabric, reducing comfort. Furthermore, the lamination of functional membranes tests the bonding strength between the membrane and the fabric components, thus affecting the durability of the fabric. Based on the existence of the above technical problems, this invention proposes an abrasion-resistant and tear-resistant mountaineering clothing fabric and its manufacturing method. Summary of the Invention
[0003] The purpose of this invention is to provide a wear-resistant and tear-resistant mountaineering clothing fabric and its manufacturing method in order to solve the problems of the prior art.
[0004] The present invention achieves the above objectives through the following technical solutions: As a first aspect of the present invention, a method for manufacturing abrasion-resistant and tear-resistant mountaineering clothing fabric is provided, comprising the following steps: (1) Preparation of base film: Silica aerogel modified with silane coupling agent is dispersed in polyurethane solution to obtain spinning solution, and then the spinning solution is electrospun to obtain base film. (2) Preparation of interwoven reinforcement layer: multiple composite metal wires A are sewn along the longitudinal parallel line of the base membrane, and then at least one composite metal wire B is arranged in the latitudinal direction in the sewn section of the composite metal wires A on the base membrane; (3) Place silane-grafted α-polyolefin hot melt adhesive film and polyester-cotton fabric in sequence on both sides of the interwoven reinforcement layer of the base film, and then composite them by hot pressing composite process to obtain the wear-resistant and tear-resistant mountaineering clothing fabric.
[0005] As a further technical solution of the present invention, in step (1), the mass of the silica aerogel modified by the silane coupling agent is 10-15% of the mass of the polyurethane, and the amount of the silane coupling agent is 2-4% of the mass of the silica aerogel.
[0006] As a further technical solution of the present invention, in step (2), the suture segments of the composite metal wires A in two adjacent rows on the basement membrane are arranged to overlap or intersect.
[0007] As a further technical solution of the present invention, in step (2), the composite metal wire A and the composite metal wire B are both prepared by electrostatic coaxial spinning with metal wire as the inner core and ultra-high molecular weight polyethylene swelling liquid with a mass fraction of 4-6% as the outer wrapping wire. The metal wire is made of either copper or stainless steel and has a fineness of 2-4D. The fineness of both composite metal wire A and composite metal wire B is 10-15D.
[0008] As a further technical solution of the present invention, the molecular weight of the ultra-high molecular weight polyethylene is 1 million to 5 million, the swelling solvent is a compound solvent of decahydronaphthalene and paraffin oil in equal volumes, the swelling treatment temperature is 80-95℃, and the swelling time is 24h.
[0009] As a further technical solution of the present invention, in step (3), the preparation method of silane-grafted α-polyolefin hot melt adhesive film is as follows: the initiator is fully dissolved in silane to obtain a solution, the solution is uniformly mixed with α-polyolefin, an antioxidant is added, and after being fully mixed, it is placed in an oil bath environment at 130±5℃, and the temperature is increased to 170-180℃ at 5℃ / min while stirring, and the reaction is continued for 10-15min to obtain the grafted product. The grafted product is then placed on a flat vulcanizing machine at 10-15MPa and 130-140℃ for 3-5min to obtain a film. The unreacted silane in the film is cleaned and removed, and the film is dried in a vacuum oven at 75-80℃ for 3-4h to obtain silane-grafted α-polyolefin hot melt adhesive.
[0010] As a further technical solution of the present invention, the amount of silane used is 4-8 phr, and the silane is a combination of vinyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane in a mass ratio of 1-2:1; the antioxidant is antioxidant 1010, and the amount used is 0.1-0.2 phr; the initiator is initiator DCP, and the amount used is 0.2-0.3 phr.
[0011] As a further technical solution of the present invention, in step (3), the temperature of hot pressing is 100-120℃, the hot pressing pressure is 0.2-0.5MPa, the hot pressing time is 10-15s, the pressure is maintained and cooled to below 60℃, and the curing is carried out for 20-24h at an ambient temperature of 25±5℃ and a relative humidity of 65±5%.
[0012] As a second aspect of the present invention, a wear-resistant and tear-resistant mountaineering clothing fabric is also provided, which is manufactured by the manufacturing method described in any one of the above claims.
[0013] The beneficial effects of this invention are as follows: This invention constructs an interwoven reinforcement layer by stitching multiple composite metal wires A along the warp parallel lines of a base membrane, and then arranging at least one composite metal wire B along the weft direction in the stitched section of the composite metal wires A on the base membrane. A silane-grafted α-polyolefin hot melt adhesive film and a polyester-cotton fabric are then sequentially placed on both sides of the interwoven reinforcement layer on both sides of the base membrane, and finally, the fabric is obtained through a hot-pressing composite process. The interwoven reinforcement layer constructs a "reinforcement network," improving the fabric's tear resistance. Furthermore, the silane-grafted α-polyolefin hot melt adhesive film strengthens the structural strength of the interwoven reinforcement layer, promoting an overall improvement in the fabric's tear resistance and abrasion resistance. The fabric exhibits good overall durability and allows for long-term performance of its tear resistance and abrasion resistance. Attached Figure Description
[0014] Figure 1 This is a schematic diagram of the interwoven reinforcement layer of fabric A provided by the present invention; in the figure, (a) is a cross-sectional view; (b) is a front view; Figure 2 A schematic diagram of the interlacing reinforcement layer of fabric B provided by the present invention; Figure 3 This is a schematic diagram of the interlacing reinforcement layer of fabric C provided by the present invention. Detailed Implementation
[0015] The present application will now be described in further detail. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above content.
[0016] All materials and reagents not specified in this invention are commercially available, and all methods not specified can be performed using conventional methods.
[0017] 1. Preparation of abrasion-resistant and tear-resistant mountaineering clothing fabrics 1.1 Preparation of the basement membrane A silane coupling agent (KH-560) was dispersed in an ethanol solvent to obtain a silane coupling agent solution with a mass fraction of 0.2%. The sprayed silane coupling agent solution was mixed with silica aerogel under vortexing conditions and then heat-treated. The spraying rate was 2 mL / s, the heat treatment temperature was 80℃, and the heat treatment time was 60 min to obtain silica aerogel modified with silane coupling agent. A spinning solution was obtained by dispersing silica aerogel modified with a silane coupling agent in a polyurethane solution. The mass of the silica aerogel modified with the silane coupling agent was 10-15% of the mass of the polyurethane (10% in the example), and the amount of the silane coupling agent was 2-4% of the mass of the silica aerogel (4% in the example). The spinning solution was then electrospun to obtain a base film. The electrospinning pressure was 12kV, the spinning solution injection speed was 0.2mm / min, the collection speed was 45r / min, the temperature was 25℃, and the relative humidity was 45% (the electrospinning process parameters of the spinning solution are those that can be adjusted by those skilled in the art according to conventional processes, but are not limited to these parameters).
[0018] 1.2 Preparation of composite metal wires Ultra-high molecular weight polyethylene powder (molecular weight of 1 million-5 million) was added to a solvent of equal volume of decahydronaphthalene and paraffin oil for swelling treatment. The temperature of the dissolution treatment was 80-95℃ and the swelling time was 2-4h (95℃, 2h was selected in the example) to obtain an ultra-high molecular weight polyethylene swelling solution with a mass fraction of 4-6% (5% was set in the example).
[0019] The inner core wire is made of copper or stainless steel, with a fineness of 2-4D. In this example, a 4D stainless steel wire is selected (obtained by twisting two stainless steel wires of the same fineness together, with a twist of 40 twists / 10cm). The outer sheath is made of ultra-high molecular weight polyethylene swelling liquid, and the composite metal wire is prepared by electrostatic coaxial spinning. The fineness of the fiber ejected from the spinning nozzle is 10-15D (10D in this example). The fiber ejected from the spinning nozzle is placed in deionized water for cooling for 2 hours.
[0020] 1.3 Preparation of the interwoven reinforcement layer Multiple composite metal wires A are sewn along the warp parallel lines of the basement membrane. The spacing between two adjacent rows of composite metal wires A is between 5-10 mm, and is set to 10 mm in this embodiment. The width of the sewn segment of a single row of composite metal wires A is between 5-10 mm, and is set to 10 mm in this embodiment. The specific number of rows of composite metal wires A and the number of sewn segments in each row are set according to the required fabric size.
[0021] The suture segments of the two adjacent rows of composite metal wires A on the basement membrane are staggered.
[0022] Along each side of the basement membrane, composite metal wire A is interwoven with two composite metal wires B in the suture segment on the basement membrane, in a parallel weft direction, as shown in the schematic diagram. Figure 1 As shown, an interwoven reinforcement layer can be formed on both sides of the basement membrane.
[0023] 1.4 Preparation of silane-grafted α-polyolefin hot melt adhesive film The initiator DCP was fully dissolved in silane to obtain a solution. The solution was then uniformly mixed with α-polyolefin (weight average molecular weight Mw = 15000 g / mol). Antioxidant 1010 was added and the mixture was thoroughly mixed. The mixture was then placed in an oil bath at 130°C and heated to 180°C at a rate of 5°C / min while stirring. The reaction was continued for 10 min to obtain the grafted product. The grafted product was then placed on a flat vulcanizing machine at 15 MPa and 130°C for 5 min to obtain a film. Unreacted silane was removed from the film, and the film was dried in a vacuum oven at 80°C for 3 h to obtain silane-grafted α-polyolefin hot melt adhesive. The silane is a combination of vinyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane in a mass ratio of 2:1, the amount of silane is 4-8 phr (5 phr in the example), the amount of antioxidant 1010 is 0.1-0.2 phr (0.1 phr in the example), and the amount of initiator DCP is 0.2-0.3 phr (0.2 phr in the example).
[0024] 1.5 Hot-pressed composite A silane-grafted α-polyolefin hot melt adhesive film and a polyester-cotton fabric are sequentially placed on both sides of the base membrane interwoven reinforcement layer, and then laminated by a hot pressing composite process to obtain the wear-resistant and tear-resistant mountaineering clothing fabric.
[0025] The polyester-cotton fabric is a 50D plain weave blend of 70% polyester and 30% cotton, with a warp and weft density of 300T.
[0026] The hot-pressing temperature is 100-120℃, the hot-pressing pressure is 0.2-0.5MPa, the hot-pressing time is 10-15s, and the pressure is maintained and cooled to below 60℃. Curing is then carried out for 20-24 hours at an ambient temperature of 25±5℃ and a relative humidity of 65±5%. In this example, the hot-pressing temperature is 110℃, the hot-pressing pressure is 0.2MPa, the hot-pressing time is 15s, the pressure is maintained and cooled to below 60℃, and curing is carried out for 24 hours at an ambient temperature of 25℃ and a relative humidity of 65%. The resulting abrasion-resistant and tear-resistant mountaineering clothing fabric is denoted as Fabric A.
[0027] 2. Verification Experiment 2.1 To investigate the impact of the interlacing reinforcement layer's structural design on fabric performance, the structure of the interlacing reinforcement layer was adjusted based on fabric A: Fabric B: The difference in manufacturing method between fabric B and fabric A lies in 1.3, the preparation of the interwoven reinforcement layer: Multiple composite metal threads A are sewn along the warp parallel lines of the basement membrane. The spacing between two adjacent rows of composite metal threads A is 10mm, and the width of the sewn segment of a single row of composite metal threads A is 10mm. The specific number of rows of composite metal threads A and the number of sewn segments in each row are set according to the required fabric size.
[0028] The suture segments of the two adjacent rows of composite metal wires A on the basement membrane are staggered.
[0029] Along each side of the basement membrane, composite metal wire A is interwoven with a composite metal wire B in the suture segment on the basement membrane, in the weft direction, as shown in the schematic diagram. Figure 2 As shown, an interwoven reinforcement layer can be formed on both sides of the basement membrane.
[0030] Fabric C: The only difference in manufacturing method from Fabric A is that the suture segments of the composite metal wires A in adjacent rows on the basement membrane overlap. Then, along the weft direction, two composite metal wires B are arranged in parallel interlacing within the suture segments of the composite metal wires A on each side of the basement membrane, as shown in the schematic diagram. Figure 3 As shown.
[0031] Fabric D: The only difference between fabric D and fabric A is that the composite metal wire B is not included.
[0032] Fabric E: The only difference from fabric A is that after forming interwoven reinforcing layers on both sides of the base film, composite metal wire B is fixed and composite metal wire A is pulled out, that is, composite metal wire A is not set.
[0033] Fabric F: The only difference between it and Fabric A is that it does not have an interlacing reinforcement layer.
[0034] The tear resistance of fabric AF was tested according to GB / T3917-1:2009 "Tear resistance of fabrics - Part 1: Determination of tear strength by impact pendulum method". Three replicates were set up for fabric AF, and the results were averaged. The results are shown in Table 1.
[0035] The abrasion resistance of fabric AF was tested, specifically according to standard GB / T21196.3-2007 "Textiles - Martindale Method - Determination of Abrasion Resistance of Fabrics - Part 3: Determination of Mass Loss". The friction loss was measured as the mass loss after 2000 abrasion cycles. The greater the friction loss, the more severe the wear and the worse the abrasion resistance of the fabric. Three replicates were set up for fabric AF, and the results were averaged. The results are shown in Table 1.
[0036] Table 1. Test results of AF tear resistance and abrasion resistance of the fabric.
[0037] As can be seen from Table 1, compared with fabric AE, the structural setting of the interlaced reinforcement layer affects the tear resistance of the fabric. Furthermore, the staggered arrangement of the stitching segments of two adjacent rows of composite metal wires A on the base film is more conducive to building a "reinforcement network" and improving the tear resistance of the fabric compared to an overlapping arrangement.
[0038] 2.2 To investigate the effect of the silane-grafted α-polyolefin hot melt adhesive film on fabric performance, the configuration of the silane-grafted α-polyolefin hot melt adhesive film was adjusted based on fabric A: Fabric G: The only difference between fabric G and fabric A is that when preparing the silane-grafted α-polyolefin hot melt adhesive film, the silane is a combination of vinyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane in a mass ratio of 1:1.
[0039] Fabric H: The only difference between it and Fabric A is that when preparing the silane-grafted α-polyolefin hot melt adhesive film, the silane is vinyltrimethoxysilane.
[0040] Fabric I: The only difference in manufacturing method from Fabric A is that α-polyolefin hot melt adhesive film is used instead of silane grafted α-polyolefin hot melt adhesive film. In the preparation of α-polyolefin hot melt adhesive film, initiator DCP is directly and uniformly mixed with α-polyolefin, antioxidant 1010 is added, and after thorough mixing, it is placed in an oil bath environment at 130℃, and the temperature is increased to 180℃ at 5℃ / min while stirring. The reaction is continued for 10min to obtain the grafted product. The grafted product is then placed on a flat vulcanizing machine at 15MPa and 130℃ for 5min to obtain a film. Unreacted silane in the film is removed, and the film is dried in a vacuum oven at 80℃ for 3h to obtain α-polyolefin hot melt adhesive. The amount of antioxidant 1010 is 0.1phr, and the amount of initiator DCP is 0.2phr.
[0041] Fabric J: The only difference between fabric J and fabric A is that TPU hot melt adhesive film (Sanxin Chemical (Wuxi) Co., Ltd.) is used instead of silane-grafted α-polyolefin hot melt adhesive film.
[0042] Fabric K: The silane-grafted α-polyolefin hot melt adhesive film used in Fabric A is placed between two layers of polyester-cotton fabric, and hot-pressed composite is carried out according to the hot-pressing composite process parameters of Fabric A to obtain the fabric. Fabric L: The TPU hot melt adhesive film is placed between two layers of polyester-cotton fabric, and the fabric is obtained by hot pressing and bonding according to the hot pressing and bonding process parameters of the same fabric A.
[0043] The tear resistance and abrasion resistance of fabric GL were also tested, and the results are shown in Table 2.
[0044] Table 2. Test results of tear resistance and abrasion resistance of fabric GL
[0045] As can be seen from Table 2, the application of silane-grafted α-polyolefin hot melt adhesive film has an impact on the tear resistance and abrasion resistance of the fabric, and is superior to the commonly used TPU hot melt adhesive film. Using α-polyolefin hot melt adhesive film without silane grafting is not conducive to improving the tear resistance and abrasion resistance of the fabric. Using vinyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane mixed graft modified α-polyolefin hot melt adhesive film is beneficial to strengthening the structural strength of the interwoven reinforcement layer, thereby promoting the overall improvement of the tear resistance and abrasion resistance of the fabric.
[0046] In addition, peel strength tests were conducted on fabrics A and FL: the peel strength test was conducted in accordance with the standard FZ / T01085-2010 "Test Method for Peel Strength of Hot Melt Bonded Interlining". In this test, an electronic single fiber strength tester was used to test the peel strength of the two layers of polyester-cotton fabric.
[0047] The sample size was 15mm × 100mm, the spacing was 10mm, and the tensile speed was 100mm / min. Five tests were performed on each sample according to the standard, and the average value was taken as the final data. The results are summarized in Table 3.
[0048] Table 3. Peel strength test results for fabric A and fabric FL
[0049] As can be seen from Table 3, comparing fabric A and fabric K, the setting of the base film and the interlacing reinforcement layer has a positive effect on improving the peel strength between the two layers of polyester-cotton fabric. In addition, the setting of the silane-grafted α-polyolefin hot melt adhesive film affects the peel strength between the two layers of polyester-cotton fabric. Using an α-polyolefin hot melt adhesive film without silane grafting is not conducive to improving the peel strength between the two layers of polyester-cotton fabric. Furthermore, the combination of vinyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane is more conducive to enhancing the peel strength between the two layers of polyester-cotton fabric, thereby improving the overall durability of the fabric and promoting the long-term performance of the fabric's tear resistance and abrasion resistance.
[0050] The above-described embodiments are merely examples of several implementations of the present invention, and their descriptions are relatively specific and detailed. However, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for manufacturing a wear-resistant and tear-resistant mountaineering clothing fabric, characterized in that, Includes the following steps: (1) Preparation of base film: Silica aerogel modified with silane coupling agent is dispersed in polyurethane solution to obtain spinning solution, and then the spinning solution is electrospun to obtain base film. (2) Preparation of interwoven reinforcement layer: multiple composite metal wires A are sewn along the longitudinal parallel line of the base membrane, and then at least one composite metal wire B is arranged in the latitudinal direction in the sewn section of the composite metal wires A on the base membrane; (3) Place silane-grafted α-polyolefin hot melt adhesive film and polyester-cotton fabric in sequence on both sides of the interwoven reinforcement layer of the base film, and then composite them by hot pressing composite process to obtain the wear-resistant and tear-resistant mountaineering clothing fabric.
2. The method for manufacturing a wear-resistant and tear-resistant mountaineering clothing fabric according to claim 1, characterized in that, In step (1), the mass of the silica aerogel modified with silane coupling agent is 10-15% of the mass of polyurethane, and the amount of silane coupling agent is 2-4% of the mass of silica aerogel.
3. The method for manufacturing a wear-resistant and tear-resistant mountaineering clothing fabric according to claim 1, characterized in that, In step (2), the suture segments of the composite metal wires A in two adjacent rows on the basement membrane are arranged to overlap or intersect.
4. The method for manufacturing a wear-resistant and tear-resistant mountaineering clothing fabric according to claim 1, characterized in that, In step (2), both composite metal wire A and composite metal wire B are prepared by electrostatic coaxial spinning with metal wire as the inner core and ultra-high molecular weight polyethylene swelling liquid with a mass fraction of 4-6% as the outer wrapping wire. The metal wire is made of either copper or stainless steel and has a fineness of 2-4D. The fineness of both composite metal wire A and composite metal wire B is 10-15D.
5. The method for manufacturing a wear-resistant and tear-resistant mountaineering clothing fabric according to claim 4, characterized in that, The ultra-high molecular weight polyethylene has a molecular weight of 1 million to 5 million. The swelling solvent is a compound solvent of decahydronaphthalene and paraffin oil in equal volumes. The swelling treatment temperature is 80-95℃ and the swelling time is 24h.
6. The method for manufacturing a wear-resistant and tear-resistant mountaineering clothing fabric according to claim 1, characterized in that, In step (3), the preparation method of silane-grafted α-polyolefin hot melt adhesive film is as follows: the initiator is fully dissolved in silane to obtain a solution, the solution is uniformly mixed with α-polyolefin, an antioxidant is added, and after being fully mixed, it is placed in an oil bath environment at 130±5℃, and the temperature is increased to 170-180℃ at 5℃ / min while stirring. The reaction continues for 10-15min to obtain the grafted product. The grafted product is then placed on a flat vulcanizing machine at 10-15MP and 130-140℃ for 3-5min to obtain a film. The unreacted silane in the film is cleaned and dried in a vacuum oven at 75-80℃ for 3-4h to obtain silane-grafted α-polyolefin hot melt adhesive.
7. The method for manufacturing a wear-resistant and tear-resistant mountaineering clothing fabric according to claim 6, characterized in that, The amount of silane used is 4-8 phr, and the silane is a combination of vinyltrimethoxysilane and γ-mercaptopropyltrimethoxysilane in a mass ratio of 1-2:1; the antioxidant is antioxidant 1010, and the amount used is 0.1-0.2 phr; the initiator is initiator DCP, and the amount used is 0.2-0.3 phr.
8. The method for manufacturing a wear-resistant and tear-resistant mountaineering clothing fabric according to claim 1, characterized in that, In step (3), the hot-pressing temperature is 100-120℃, the hot-pressing pressure is 0.2-0.5MPa, the hot-pressing time is 10-15s, the pressure is maintained and cooled to below 60℃, and the curing is carried out for 20-24h at an ambient temperature of 25±5℃ and a relative humidity of 65±5%.
9. A wear-resistant and tear-resistant mountaineering clothing fabric obtained by the manufacturing method described in any one of claims 1-8.